Effects of intercropping desho grass with vetch on forage yield, nutritional quality and soil fertility in Lemo District of Hadiya Zone, Southern Ethiopia - Berhanu, Melkamu (Wachemo University, 2022)
This experiment was conducted in Hadiya Zone, Lemo district of southern Ethiopia with the objectives of evaluating the effects of intercropping desho grass with vetch (v.villosa) on forage yield, nutritional quality and soil fertility. The experiment was conducted in a randomized complete block design with three replications. Soil samples were collected before planting and after forage harvest. The treatments were desho vetch intercropping at a 12kg/ha seed rate for vetch (T1), desho vetch intercropping at a 9kg/ha seed rate for vetch (T2), desho vetch intercropping at 6kg/ha seed rate for vetch (T3), sole desho grass (T4) and sole vetch (T5). Data on biomass yield; plant height and chemical compositions were recorded and analyzed using the General Linear Model procedures of SAS. Relative yield, relative yield total, and aggressivity index were calculated for biological compatibility and yield advantages of desho and vetch (V.villosa). The pre- sowing soil analysis showed that the experimental soil had average pH of 6.73. This indicates that the soil was slightly acidic. Intercropping vetch with desho grass resulted in significantly higher total dry matter yield than sole desho grass at all cutting stages. The highest total dry matter yield (16.04-26.3 t/ha) was obtained from T1. The highest forage CP content (%) was obtained from T1 (10.07-13.45%) at all harvesting stages. On the other hand, significantly (P<0.05) higher ADF, ADL and NDF contents (%) was obtained from sole desho grass. Significantly higher in vitro organic matter digestibility (IVOMD) was obtained from intercropped desho grass with vetch (T1; 60.24, T2; 58.54 and T3; 60.03) at all cutting stages compared to the pure stand. The relative yield total of desho-vetch mixtures were greater than one, showing a yield advantage over the pure stand. The higher organic carbon percentage in tested soil after forage harvest in all vetch based treatments was probably due to improved soil fertility. The intercropping at a 12kg/ha seed rate for vetch has the potential to provide maximize production and productivity in study area and thus can be recommended for further evaluation and application.